2006
DOI: 10.1111/j.1600-0609.2006.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytosis in obese individuals: possible link in patients with unexplained persistent neutrophilia

Abstract: Obesity is recognized as a possible cause for reactive leukocytosis. Awareness of this 'obesity-associated leukocytosis' may help the clinician to avoid more extensive and unnecessary diagnostic work-up, particularly in similar obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 26 publications
(28 reference statements)
7
102
3
2
Order By: Relevance
“…In support of previous findings, the positive associations between the number of cells and obesity have been reported in a number of cross sectional studies [15,21]. For example, Herishanu et al study [22] found that from among several factors responsible for persistent leukocytosis, such as smoking, myeloproliferative and lymphoproliferative disease, obesity would be the only identified cause.…”
Section: Discussionsupporting
confidence: 66%
“…In support of previous findings, the positive associations between the number of cells and obesity have been reported in a number of cross sectional studies [15,21]. For example, Herishanu et al study [22] found that from among several factors responsible for persistent leukocytosis, such as smoking, myeloproliferative and lymphoproliferative disease, obesity would be the only identified cause.…”
Section: Discussionsupporting
confidence: 66%
“…There are many conditions in which a high inflammatory state has been reported to be associated with AR dilatation,33, 34 thus the correlation between ARD and markers of inflammation, such as neutrophil percentage in the present study, was not a surprise 35. Our understanding of the role of the neutrophil in inflammation has changed fundamentally in recent years.…”
Section: Discussionmentioning
confidence: 46%
“…Obesity is associated with increased plasmatic concentration of several proinflammatory mediators and of calcitonin gene-related protein. 38,39 Furthermore, relative to normal weight, obese migraineurs have attacks of increased frequency and severity, 29 which may explain the higher prevalence of CA in obese individuals. Of note is the age-related decrease in CA.…”
Section: Discussionmentioning
confidence: 99%